2019
DOI: 10.1080/00221309.2018.1535485
|View full text |Cite
|
Sign up to set email alerts
|

Passive smoking is associated with cognitive and emotional impairment in adolescent girls

Abstract: It is well established that smoking is associated with impaired mental health and sleep problems. However the possible effects of passive smoking on cognitive and emotional characteristics have not previously been evaluated in adolescents. We investigated the association between passive smoking and cognitive and emotional function, and sleep patterns in 940 adolescent girls. The girls were divided into 2 groups [305 exposed subjects and 635 non-exposed subjects (the controls)]. The passive smokers had a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
1
13
0
2
Order By: Relevance
“…Similar findings were reported in other studies that the risk of smoking tobacco was increased in adolescents with aggressive dispositions ( Kelishadi et al, 2015 ; Whalen et al, 2001 ). Moreover in this study, a comparatively higher proportion of exposure to second-hand smoke was seen in physically violent adolescents as compared to the non-aggressive ones, this was in agreement with another study which evidenced that adolescent girls who are comparatively more exposed to second-hand smoke are more likely to have aggressive behaviors ( Khorasanchi et al, 2019 ). The probable reason for this association might be the mood swings and addictive tendencies associated with aggression.…”
Section: Discussionsupporting
confidence: 93%
“…Similar findings were reported in other studies that the risk of smoking tobacco was increased in adolescents with aggressive dispositions ( Kelishadi et al, 2015 ; Whalen et al, 2001 ). Moreover in this study, a comparatively higher proportion of exposure to second-hand smoke was seen in physically violent adolescents as compared to the non-aggressive ones, this was in agreement with another study which evidenced that adolescent girls who are comparatively more exposed to second-hand smoke are more likely to have aggressive behaviors ( Khorasanchi et al, 2019 ). The probable reason for this association might be the mood swings and addictive tendencies associated with aggression.…”
Section: Discussionsupporting
confidence: 93%
“…Exposure to passive smoking can increase the risk of developing or dying from diseases such as cancer (particularly lung and breast cancer) and cardiovascular diseases (e.g., stroke, angina, and hypertension), as well as cognitive impairment [3][4][5]. Positive correlations between tobacco exposure and cognitive impairment, dementia, and other neurodegenerative diseases have also been reported [6,7]. However, some studies have suggested a protective role of nicotine against cognitive impairment [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Furthermore, secondhand smoke exposure was also associated with poor mental health according to a stratified analysis of smoking status. In previous studies, secondhand smoke exposure was associated to sleep problems (insomnia or caused by psychosocial stress), 35,36 depression, 10,37 and planned or attempted suicide. 22 Although the intensity of the effect of secondhand smoke exposure on mental health varied according to smoking status, secondhand smoke exposure was associated with an increase in mental health problems.…”
Section: Discussionmentioning
confidence: 91%